Distinct functions of junD in cardiac hypertrophy and heart failure - Ricci, Romeo (Cold Spring Harbor Laboratory Press, 2005)
Cardiac hypertrophic stimuli induce both adaptive and maladaptive growth response pathways in heart. Here we show that mice lacking junD develop less adaptive hypertrophy in heart after mechanical pressure overload, while cardiomyocyte-specific expression of junD in mice results in spontaneous ventricular dilation and decreased contractility. In contrast, fra-1 conditional knock-out mice have a normal hypertrophic response, whereas hearts from fra-1 transgenic mice decompensate prematurely. Moreover, fra-1 transgenic mice simultaneously lacking junD reveal a spontaneous dilated cardiomyopathy associated with increased cardiomyocyte apoptosis and a primary mitochondrial defect. These data suggest that junD promotes both adaptive-protective and maladaptive hypertrophy in heart, depending on its expression levels.